Metabolomics of ethnic fermented foods and beverages: understanding new aspects through Omic techniques - Sarkar, Sagnik; Sha, Shankar Prasad; Ghatani, Kriti (Frontiers in Sustainable Food Systems, 2023)
In the era of ethomics, genomics, metagenomics, metabolomics, transcriptomics, proteomics, cheesomics, have emerged as powerful tools for the deep analysis of microbial diversity and functionality of different fermented foods and beverages. However, these two are quite new in the field of science, but they are already proven to be crucial for better understanding of microbes, their interactions with hosts and surrounding environments, metabolic activity and intracellular biochemical reactions. It not only provides brief knowledge about the physicochemistry of the particular organism but also gives a clear overview of the abundance of proteins, their encoding genes and their functional attributes. Metabolomics is a quantitative and qualitative determination study of metabolites of participating microbes in the process of fermentation that helps to analyse several biochemical pathways with respect to chemical changes that occur during different stages of fermentation. Thus, it gives a deep insight into the microscopic world as well as helps to further enhance the available nutraceuticals and probiotic characterizations in the fermented foods. Metabolomics study can be used to modify strains as per the needs for example, different stress tolerant microbial strains for the optimal production of desired metabolites in stressed conditions, modulation in metabolic pathways to increase bioavailability of important compounds etc. Present review aimed to provide insights into metagenomics and metabolomics approaches that are currently playing a vital role in microbial diversity and their functionality attributes for improving human health and sustainability of fermented foods and Alcoholic beverages.